Urinary Bisphenol A Levels and Male Fertility. Issue 6 (November 2018) - Radwan, Michał; Wielgomas, Bartosz; Dziewirska, Emila; Radwan, Paweł; Kałużny, Paweł; Klimowska, Anna; Hanke, Wojciech; Jurewicz, Joanna
Bisphenol A (BPA) is a high-production volume industrial chemical found in many consumer products. BPA is a suspected potent endocrine disruptor, with endocrine-disrupting properties demonstrated in animal studies. Few human studies have examined bisphenol A exposure in relation to male fertility and, results are divergent. The aim of the study is to examine the associations between urinary BPA concentration and male fertility. Bisphenol A urinary concentrations were measured using gas chromatography coupled with tandem mass spectrometry in 315 men under 45 years of age with normal sperm concentration (⩾15 mln/ml) recruited from a male reproductive health clinic. Participants were interviewed and provided a semen sample. BPA was detected in 98.10% of urine samples, with a median concentration of 1.87 µg/l (1.63 µg/ g creatinine). A multiple linear regression analysis identified a positive association between the urinary concentrations of bisphenol A 25th–50th percentile and total sperm sex chromosome disomy ( p = .004). Also when modeled as continuous variable urinary BPA concentration increased total sperm sex chromosome disomy ( p = .01). Urinary concentration of BPA also increase the percentage of immature sperm (HDS) ( p = .018) and decrease motility ( p = .03). The study provides evidence that exposure to BPA is associated with poorer semen quality. Future studies are needed to confirm these findings.